Composición florística en potreros de Los Tuxtlas, Veracruz, México - Lira-Noriega, Andrés; Guevara, Sergio; Laborde, Javier; Sánchez-Ríos, Graciela (Instituto de Ecología, A.C., 2007)
An inventory of the angiosperm and fern plant species growing in areas deprived of trees in pastures of Los Tuxtlas mountain range is presented. In order to obtain a complete floristic list, sampling was carried out during both the dry and wet seasons of 1992, in pastures of two localities: Balzapote and La Palma. At each locality, five pastures dominated by native grass species (known locally as grama pastures) and five dominated by the introduced African star grass, Cynodon plectostachyus (known as star pastures), were selected. In each pasture ten 2 x 2 m sampling plots were randomly established within one hectare, recording the cover of every species present within each quadrat, in addition vegetation height was measured. A total of 200 angiosperm and 14 fern species, belonging to 55 families, was recorded. The families with 10 or more species were Asteraceae, Euphorbiaceae, Poaceae and Leguminosae (sensu lato). The species with cover greater than 10% of sampled area were C. plectostachyus, Axonopus spp., Paspalum conjugatum (Poaceae), Hyptis atrorubens (Lamiaceae), and Mimosa pudica (Leguminosae: Mimosaceae). Most species found in pastures were weeds and grasses; however, seedlings of tree and shrub species were also found.